Health insurance coverage and its awareness among population in the rural field practice area of Adichunchanagiri Institute of Medical Sciences, B G Nagara, Karnataka - Manuja, L. M.; Viswanatha, P. G.; Nagendra, Kanchana (International Journal Of Community Medicine And Public Health, 2019)
Background: In India, there is marked lack of awareness of health insurance in the rural and low socioeconomic sector due to reasons like the existing burden on the poor making them reluctant to think of the credit policies that are actually issued in their interest, illiteracy, lack of exposure and the growth of the private sectors has an upper hand over public sectors. Hence this study was done with the objective to determine the health insurance coverage and its awareness including perception among the rural population around Adichunchanagiri Institute of Medical Sciences, BG Nagara, Mandya. Methods: This cross sectional study was carried out among 295 households in the rural field practice area of Adichunchanagiri Institute of Medical Sciences, B G Nagara for a period of 3 months. Personal interview of the households was done using pretested semi structured questionnaire after obtaining the consent. Data was entered in MS excel and descriptive statistical measures like percentage, mean, and standard deviations were calculated. An inferential statistical measure like Chi square test was applied. Results: Among 295 households, Male constituted 49.5% and Hindus were 94.9%. 44.7% of the families were enrolled to health insurance schemes and 75.0% of them use to renew their health insurance scheme regularly. The factors which were significantly associated with health insurance enrollment and awareness were gender, education, occupation, hospitalization during last year and socioeconomic status. Only 173 (58.6%) of the respondents were aware of health insurance. Conclusions:More than half of the study population was covered by health insurance policies and majority of them were unaware of the available insurance schemes, risks and benefits of the same.